Lean six sigma in higher education : a practical guide for continuous improvement professionals in higher education - Antony, Jiju (Bingley, U.K. : Emerald Publishing Limited, 2020)
This book illustrates the integration of both Lean and Six Sigma as a process excellence methodology which can be utilized in Higher Education environments for achieving and sustaining world class efficiency and effectiveness. It showcases various studies carried out by leading research scholars, academics and practitioners.
Prelims -- Chapter 1 An overview of lean six sigma -- Chapter 2 Academic leadership their culture and characteristics -- Chapter 3 Lean six sigma in higher education: state-of-the-art findings and agenda for future research -- Chapter 4 Challenges in the deployment of LSS in the higher education sector: viewpoints from leading academics and practitioners -- Chapter 5 Readiness factors for the implementation and deployment of lean six sigma (or operational excellence) in higher education -- Chapter 6 Basic lean six sigma tools for higher education -- Chapter 7 Perceived non-value added activities in the research grant application process through a lean six sigma lens -- Chapter 8 Voice of the customer in higher education -- Chapter 9 A lean six sigma maturity model for higher education institutions -- Chapter 10 Lean six sigma roadmap for implementation in higher education sector -- Chapter 11 Six sigma and big data -- Chapter 12 Case studies of lss in higher education -- Index.
Includes index.
Print version record.
Keywords: Universities and colleges -- Administration; Education -- Higher; Colleges of higher education